Performance of Recycled Concrete Aggregate in Self Compacting Concrete - V. Arul Prakash, T.; M. Natarajan, Dr.; T. Senthil Vadivel, Dr.; Vivek, K. (International Journal of Engineering and Technology, 2018)
This article presents the influence of the Recycled Concrete Aggregate (RCA) on the mechanical properties of self-compacting fly ash concrete (M30 Grade). The RCA from local construction demolition site were employed as a replacement for natural coarse aggregate (0% - 30%) in self-compacting concrete (SCC). The Viscosity modifying material used in this study was Class F fly ash. The results indicate that recycled concrete aggregate can be replaced by an optimal 25% replacement percentage in the manufacture of SCC without significantly affecting strength and durability.Â Â